Impact of glazing area on the thermal performance of buildings - Ozel, Meral (Taylor & Francis Ltd, 2020)
In this paper, the impact of glazing area on the thermal performance of buildings is numerically investigated by considering orientation, wall insulation and type of glazing. The investigation is carried out for all months of the year in the climatic conditions of Elazig, Turkey. Firstly, the transmission loads through the wall are calculated using an implicit finite difference method. Secondly, the transmission loads through the window glass are also calculated for single and double glass. Then, while the glazing area percentage (GAP) is increased from %0 to %100, the transmission loads are determined according to the type of glazing for uninsulated and insulated walls. It is seen that in single glazing, as GAP increases, the heating and cooling transmission loads increase for all wall orientations. The results show that double glazing provides a significant reduction in especially the heating load for all building orientations when compared to single glazing.
Keywords: Heating and cooling transmission loads; building orientations; glazing area percentage; single and double glazing; insulation thickness